Features of trade credit - Білько, Олександр Павлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
Some questions of relations of credits are examined in the article. The decision of relations of credits, their kinds, features and influence, is pointed on economic development of the state.